Metformin Versus Insulin for Gestational Diabetes: Cognitive and Neuropsychological Profiles of Children Aged 9 years - Paavilainen Elisa; Nyman Anna; Niinikoski Harri; Nikkinen Hilkka; Veijola Riitta; Vääräsmäki Marja; Tossavainen Päivi; Rönnemaa Tapani; Tertti Kristiina (Williams & Wilkins, 2025)
OBJECTIVE
We compared cognitive profile and neuropsychological performance in 9-year-old offspring of mothers who were treated with metformin or insulin for gestational diabetes mellitus (GDM).
METHODS
A total of 172 children whose mothers were randomly assigned to receive either metformin or insulin for GDM were studied at the age of 9 years. Of these children, 127 were from Turku, Finland (63 metformin and 64 insulin), and 45 from Oulu, Finland (19 metformin and 26 insulin). Clinical and demographic background characteristics were obtained at enrolment, birth, and 9-year follow-up. Cognitive profiles were examined at age 9 years with the Wechsler Intelligence Scale for Children. Neuropsychological functions were examined with 2 subtests of the Developmental Neuropsychological Assessment test battery assessing comprehension of instructions and narrative memory, Trail Making Test assessing attention and with Behavioral Rating Inventory of Executive Functioning, including parent-rated and teacher-rated evaluations. Academic functioning was studied with reading fluency subtest of the Screening test for reading, writing, and calculus for first to sixth grades and information about educational support received at school reported by parents.
RESULTS
The cognitive profiles, including indexes of verbal comprehension, perceptual reasoning, working memory, and processing speed, did not differ significantly between metformin-treated and insulin-treated groups. Significant differences were not found between the treatment groups in assessed neuropsychological functions, reading fluency, or received level of support at school.
CONCLUSION
Cognitive and neuropsychological outcomes were similar in 9-year-old children whose mothers had either metformin or insulin treatment of GDM.